2014
DOI: 10.1371/journal.pone.0087329
|View full text |Cite
|
Sign up to set email alerts
|

Non-Replicating Mycobacterium tuberculosis Elicits a Reduced Infectivity Profile with Corresponding Modifications to the Cell Wall and Extracellular Matrix

Abstract: A key feature of Mycobacterium tuberculosis is its ability to become dormant in the host. Little is known of the mechanisms by which these bacilli are able to persist in this state. Therefore, the focus of this study was to emulate environmental conditions encountered by M. tuberculosis in the granuloma, and determine the effect of such conditions on the physiology and infectivity of the organism. Non-replicating persistent (NRP) M. tuberculosis was established by the gradual depletion of nutrients in an oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 62 publications
7
57
0
Order By: Relevance
“…1). The OD data were consistent with the cfu measurements and indicated a constant viable count of culturable cells, which is associated with data found for non-replicating persistence (NRP) 1 (Chao & Rubin, 2010;Shi et al, 2010;Bacon et al, 2014). The exception was M. phlei that showed a decline of growth from 1 day to 2 days after the log phase followed by constant values until 28 days suggesting a death phase before the switch to NRP (Bacon et al, 2014).…”
Section: Growth Properties Under Aerated and Hypoxic Cultivationsupporting
confidence: 86%
“…1). The OD data were consistent with the cfu measurements and indicated a constant viable count of culturable cells, which is associated with data found for non-replicating persistence (NRP) 1 (Chao & Rubin, 2010;Shi et al, 2010;Bacon et al, 2014). The exception was M. phlei that showed a decline of growth from 1 day to 2 days after the log phase followed by constant values until 28 days suggesting a death phase before the switch to NRP (Bacon et al, 2014).…”
Section: Growth Properties Under Aerated and Hypoxic Cultivationsupporting
confidence: 86%
“…With a lipid-rich cell wall envelope, mycobacterial cell wall remodeling is also tightly associated with its lipid metabolism (45) and can be a possible adaptive mechanism of M. tuberculosis when coping with a constantly changing host environment (46). In line with the apparent nonreplicative state of iLivE M. tuberculosis, we detected a downregulation of pks2 and desA3 (Table 3), which are essential genes for the biosynthesis of main cell wall components of mycobacteria (47).…”
Section: Resultssupporting
confidence: 52%
“…Finally, the increased infectivity of StarvM.tb in this study is in contrast to another recent study (39) (using the guinea pig TB model), where nonreplicating M. tuberculosis was established by the gradual depletion of nutrients in an oxygenreplete environment. In this study, it was found that the nonreplicating M. tuberculosis elicited a significantly reduced infectivity (39). Taken together, these contrasting results may reflect the different methods used to establish a dormant form of M. tuberculosis, and exactly how these different dormant forms of M. tuberculosis are present in humans during a latent (or chronic) infection is important to establish in future studies.…”
Section: Discussionmentioning
confidence: 67%